Features of modern algorithm of examination and treatment patients with endo-perio lesions (Эндодонтия Today)
Endodonto-periodontal lesions, as a result of the close anatomical and topographic communication is a complex, which is diffi cult not only to diagnose, but also to treat. The reason of the pathological changes in the pulp and periodontal tissues may be a variety of factors such as exogenous and endogenous origin, but the main one is microbial [19]. Therefore, the main principle of treatment patients with this pathology is a one-time removal of infection from the root canal system, and of pathological periodontal pockets. A particularly important aspect in the stages of diagnosis and treatment are additional methods of investigation that allow to fully assess the initial clinical situation, and to analyze the quality of the treatment. In view of the above, it increases the need for CT in order to obtain complete and accurate information. Therefore, the aim of the study was to evaluate the eff ectiveness of using CT to adequately display the anatomy of the root canal and the structural features of furcation area, as well as the level of bone resorption compared with intraoral radiographs and contact orthopantomography.